Principal’s Academic Supervision: Enhancing Teachers’ Pedagogical Competence in Junior High Schools - Hairun Najwa; Siti Raudhatul Jannah; Hamdi Zas Pendi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study investigates the implementation of academic supervision by the principal in enhancing teachers’ pedagogical competence at State Junior High School. The quality of education is closely associated with the effectiveness of the learning process, and academic supervision plays a strategic role in strengthening teachers’ professional capacity. Employing a qualitative descriptive approach, the study explores the stages of planning, implementation, and evaluation of academic supervision conducted by the principal. Data were collected through classroom observations, semi-structured interviews, and document analysis involving the principal, the vice principal for curriculum affairs, and teachers. The data were analyzed through systematic processes of data reduction, data display, and thematic conclusion drawing, supported by triangulation and member checking to ensure validity and credibility. The findings indicate that academic supervision was implemented systematically and continuously. In the planning stage, the principal developed a structured supervision program, determined schedules and instruments, and integrated professional development activities such as workshops and training sessions. During the implementation stage, supervision was carried out through classroom observations, clinical and individual supervision, and reflective dialogue sessions that provided constructive feedback. The evaluation stage was conducted periodically to assess teachers’ progress and determine appropriate follow-up actions. The results demonstrate measurable improvements in lesson planning, instructional strategies, classroom management, and assessment practices. Despite challenges such as limited time and teachers’ workload, academic supervision made a significant contribution to enhancing pedagogical competence and strengthening the overall quality of the learning process.